Under Invoicing dalam Perdagangan Internasional: Tinjauan Literatur mengenai Dampaknya terhadap Perekonomian Makro dan Kebijakan Pengawasan Perdagangan di Indonesia - Nuraifa Umaya Santi; Restiara Oktaviana Resti; Muh. Imran; Otong Karyono (Universitas Persada Indonesia YAI, 2026)
Under invoicing is a form of trade misinvoicing in which the declared value of imported or exported goods is intentionally reported below the actual transaction value. This practice is commonly employed to reduce customs duties, import taxes, and foreign exchange reporting obligations, thereby generating significant economic losses for the state. From a macroeconomic perspective, under invoicing affects not only government revenue but also the accuracy of trade statistics, foreign exchange reserves, exchange rate stability, investment climate, and the effectiveness of fiscal and trade policies. This study aims to examine the practice of under invoicing in international trade, identify its driving factors, and analyze its implications for Indonesia’s macroeconomic performance and trade supervision policies. This study employs a secondary research method using a literature review approach. Data were collected through a systematic review of reputable international journals indexed by Scopus, nationally accredited journals indexed by SINTA, reports published by international organizations such as the International Monetary Fund (IMF), the World Bank, the World Trade Organization (WTO), the Organisation for Economic Co-operation and Development (OECD), the United Nations Conference on Trade and Development (UNCTAD), and relevant Indonesian regulations. The data were analyzed using content analysis through identification, comparison, synthesis, and interpretation of previous research findings. The findings indicate that under invoicing is driven by economic incentives, weak regulatory oversight, information asymmetry, and regulatory loopholes exploited by trading actors. The practice reduces government revenue from customs and taxation, distorts international trade statistics, weakens foreign exchange reserves, increases the risk of trade misinvoicing, undermines the effectiveness of macroeconomic policies, and decreases investor confidence in trade governance. Therefore, strengthening trade supervision through digital technology, integrated inter-agency databases, risk-based monitoring systems, and enhanced international cooperation in information exchange is essential to minimize under invoicing practices in Indonesia. Keyword : Under Invoicing, International Trade, Macroeconomics, Trade Misinvoicing, Trade Policy.